Forest structure, timber species regeneration, and timber volume dynamics along a logging gradient in a lowland tropical rainforest in Africa: Implications for biodiversity conservation and sustainable timber management - David Ocama Kissa; Emmanuel Fred Nzunda; Mnason Tweheyo; Daniel Lussetti; Enock Ssekuubwa; Douglas Sheil (PLoS ONE, 2025)
Timber production, cutting and extraction is impacting vast areas of tropical forests, highlighting the need for management strategies to promote sustainable recovery of logged forests. However, limited information is available on how logging and enrichment planting affect forest structure, commercial tree species, and timber volume recovery. In this study, we assessed the effects of timber cutting and extraction (“logging”) on forest structure, regeneration of key timber species, and volume recovery across different logging intensities. We compared the effects of enrichment planting, initiated over 60 years ago, versus natural regeneration on timber volume recovery of Khaya anthotheca (Welw.) C.DC., a highly targeted species. We inventoried all live stems with a diameter at breast height (DBH) of ≥2 cm across 9 compartments using 45 plots of 0.5 ha each: heavily logged forests (25 plots, totaling 12.5 ha), lightly logged forests (15 plots, totaling 7.5 ha), and unlogged forest (5 plots, totaling 2.5 ha). Our results suggest that timber production has impacted on tree regeneration of harvested timber species such Entandrophragma species, Milicia excelsa (Welw.) C. Berg, Olea capensis L. subsp. welwitschii (Knobl.) Friis & Green and Ricinodendron heudelotii (Baill.) Heckel; Timber volume recovery of harvested species was 61.3% lower in heavily logged and 51.7% lower in lightly logged forests compared to unlogged forest. Stem density, basal area, and timber volume recovery of mahogany species were influenced by time since last logging. Notably, the compartment which was logged earlier in 1945 and enriched with K. anthotheca showed significantly higher stem density and timber volume of this species compared to logged forests without such enrichment. In conclusion, our study suggests that passive regeneration in Budongo’s logged compartments has been inadequate for achieving timber volume recovery of high-value commercial species. If an economic assessment proves favorable we recommend further trials of enrichment planting of high-value timber species (Mahogany spp., Milicia excelsa , and Olea capensis ) alongside fast-growing species ( Maesopsis eminii Engl., Albizia spp.). As well as Reduced Impact Logging and broader species selection from classes II and III, to reduce damage and enhance timber yields in production forests.